Rates of endoscopic uptake, cancer detection and early cancer proportion for global, regional and national gastric cancer screening programs: a systematic review and meta-analysis - Jiayue Wang; Xianzhu Zhou; Yiqi Du (The Lancet Regional Health. Western Pacific)
Background: Over the past three decades, hundreds of gastric cancer (GC) screening programs have been launched globally. No comprehensive study has summarized and compared the outcomes of available screening programs and identified factors potentially influencing the cancer-preventive effects. Methods: This meta-analysis aims to evaluate the temporal and geographical patterns of three key indicators within global GC screening programs: rate of endoscopic uptake, GC detection, and early cancer proportion (the rate of early GC among all GC detected), along with factors influencing the efficiency of GC screening. We systematically searched PubMed, Embase, Web of Science, and Scopus for relevant articles published until September 20, 2023. Original articles that provided sufficient data to calculate indicators in the general screening population were included. Pooled random-effect estimates of the indicators were computed, with further subgroup analysis stratified by study period, country or region, setting, screening interval, education level and socioeconomic status. This study was registered with PROSPERO (CRD42023464921). Findings: A total of 91 studies were included in the analysis: 60 reported endoscopic uptake rates, 68 reported GC detection rates, and 33 reported early GC detection rates. The overall rates were as follows: endoscopic uptake at 46.89% (95% CI: 41.40-52.39%), GC detection at 0.62% (95% CI: 0.46-0.80%), and early cancer detection at 61.41% (95% CI: 51.42-71.40%). A gradual increase in endoscopic uptake rate was observed over time; however, both GC detection and early GC detection rates exhibited a counterintuitive decline. Developed countries, such as Japan and Korea, demonstrated notably superior performance across all three indicators compared to developing countries, including China. Japan and Korea displayed time trends aligned with the prevailing global trend, whereas China exhibited notable deviations. Furthermore, factors such as screening settings, screening intervals, public campaigns, endoscopic techniques, as well as individual education and socioeconomic status significantly influenced these indicators. Interpretation: Countries vary considerably in their implementation of GC screening, each exhibiting unique characteristics. The rates of endoscopic uptake, cancer detection, and early GC proportions can serve as essential benchmarks for evaluating the effectiveness of GC screening programs. However, it is essential to establish customized cutoff values that are thoughtfully aligned with the specific developmental contexts of each country.